Interreligious marriage in Wollo, Ethiopia: Historical factors underpinning its development and prevalence - Muluneh Animut Tilahun; Mellese Madda Gatisso; Abdu Mohammed Ali (Social Sciences and Humanities Open)
Interreligious marriage, particularly between Christians and Muslims, has centuries-old history in Wollo and has become the unique attribute of the area that significantly shaped the socio-cultural and demographic landscape. This study aims to examine the different historical factors or events that contributed to the development and prevalence of interreligious marriages in Wollo, Ethiopia. The study employed a historical ethnographic study design and gathered primary data through in-depth interviews and focus group discussions with local elders, religious fathers, and historians who were selected via purposive and snow-ball sampling techniques. Besides, different historical documents and materials were also reviewed to substantiate the study with relevant secondary data. Hence, the study reveals that the history of Wollo represents a unique model of religious coexistence where centuries of interaction between Christians and Muslims have nurtured a culture of tolerance, shared traditions, and mutual respect. In addition, the prominence of Sufi Islam and its attributes of inclusivity and adaptability; the cultural blending and religious intermixing after the military campaign of Ahmed Gragn; the ethnic and cultural integration sparked by the Oromo population movement into the area; and the various religious policies adopted by successive monarchical rules after the Zemen Mesafint were the major historical factors contributing for the development and prevalence of interreligious marriage in Wollo. Thus, the study implies that that religious tolerance and social harmony could flourish in diversified societies when religious communities prioritize shared values and mutual respect over doctrinal differences. Finally, the study concludes that by creating interfaith forums and discussion groups, organizing collaborative cultural and religious festivals, facilitating adaptive religious practices, preparing continuous cultural exchange and experience-sharing programs and others, it is possible to produce positive results in other areas with religious diversities.